2016
DOI: 10.1177/1753425916668244
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A attracts inflammatory cells in murine lung infection with P. aeruginosa

Abstract: IL-17A-dependent immunity is of importance in the protection against extracellular bacterial pathogens. However, IL-17A is also suggested to mediate the pathogenesis of lung diseases, such as acute respiratory distress syndrome. Here, we studied the role of IL-17A in a mouse model of acute pneumonia. IL-17A mediated the expression of keratinocyte-derived chemokine (KC) and the recruitment of inflammatory cells in mice infected with a sub-lethal dose of Pseudomonas aeruginosa. IL-17A deficiency protected mice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Although the beneficial vs. detrimental role of IL-17 signaling (e.g. in IL-17 −/− or IL-17R −/− mice) in acute P. aeruginosa infection is still debated [57,58], the absence of IL-17 signaling has been linked to increased incidence of chronic P. aeruginosa infection, increased bacterial burden and decreased survival in recent studies [59,60]. Lore, et al noted, however, that chronically infected IL-17a −/− mice showed less pulmonary inflammation and tissue damage than wild-type counterparts, consistent with IL-17-mediated increases in matrix metalloproteinase secretion and tissue remodeling [61].…”
Section: Immune Recognition and Response To P Aeruginosa Infectionmentioning
confidence: 99%
“…Although the beneficial vs. detrimental role of IL-17 signaling (e.g. in IL-17 −/− or IL-17R −/− mice) in acute P. aeruginosa infection is still debated [57,58], the absence of IL-17 signaling has been linked to increased incidence of chronic P. aeruginosa infection, increased bacterial burden and decreased survival in recent studies [59,60]. Lore, et al noted, however, that chronically infected IL-17a −/− mice showed less pulmonary inflammation and tissue damage than wild-type counterparts, consistent with IL-17-mediated increases in matrix metalloproteinase secretion and tissue remodeling [61].…”
Section: Immune Recognition and Response To P Aeruginosa Infectionmentioning
confidence: 99%
“…TH17 cells can release a large amount of IL‐17A to promote G‐CSF and KC secretion, and G‐CSF can mobilize neutrophils from the bone marrow to peripheral blood . KC can induce the chemotaxis of pro‐inflammatory cells in particular neutrophils to the lung, consequently increasing inflammatory monocytes and neutrophils and lymphocytes in the BALF of the mice with AE‐IPF and exacerbating the local inflammatory responses in the lung. Compared with the WT mice, the IL‐17A ‐/‐ mice showed reduced G‐CSF and KC concentrations in the BALF, fewer inflammatory monocytes and neutrophils in the BALF, attenuated lung inflammation and dysfunction and higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, IL-17A is nearly undetectable in naïve infants, and vaccination increases IL-17A levels (14). Mice deficient in IL-17A and IL-17RA demonstrate increased susceptibility to a large number of bacterial pathogens that cause lung diseases (15, 16). Even so, the mechanism of IL-17A production during S. pneumoniae infection is largely unknown.…”
Section: Introductionmentioning
confidence: 99%